2021
DOI: 10.3390/cancers13092131
|View full text |Cite
|
Sign up to set email alerts
|

IFN-γ Critically Enables the Intratumoural Infiltration of CXCR3+ CD8+ T Cells to Drive Squamous Cell Carcinoma Regression

Abstract: Ultraviolet (UV) radiation-induced tumours carry a high mutational load, are highly immunogenic, and often fail to grow when transplanted into normal, syngeneic mice. The aim of this study was to investigate factors critical for the immune-mediated rejection of cutaneous squamous cell carcinoma (SCC). In our rejection model, transplanted SCC establish and grow in mice immunosuppressed with tacrolimus. When tacrolimus is withdrawn, established SCC tumours subsequently undergo immune-mediated tumour rejection. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…No difference between groups in percentage of cells with Mcl-1 expression ( P = 1.00), Bcl-xL expression intensity ( P = 0.134), or the percentage of cells with Bcl-xL expression ( P = 1.00). Tacrolimus Zeng et al. 2021 Mice treated with tacrolimus IFN-γ–neutralization abrogated SCC regression, significantly reduced CD8+ T-cell infiltration into SCC, and significantly impaired the secretion of CXCL9, CXCL10, and CCL5 within the tumor microenvironment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…No difference between groups in percentage of cells with Mcl-1 expression ( P = 1.00), Bcl-xL expression intensity ( P = 0.134), or the percentage of cells with Bcl-xL expression ( P = 1.00). Tacrolimus Zeng et al. 2021 Mice treated with tacrolimus IFN-γ–neutralization abrogated SCC regression, significantly reduced CD8+ T-cell infiltration into SCC, and significantly impaired the secretion of CXCL9, CXCL10, and CCL5 within the tumor microenvironment.…”
Section: Resultsmentioning
confidence: 99%
“…(2015) revealed increased signaling of Nfatc1 in CsA-treated mice, with associated increased spontaneous SCC formation ( Goldstein et al., 2015 ). Other murine studies found that tacrolimus-treated mice showed higher numbers of chromosomal aberrations than CsA, sirolimus, and mycophenolate ( Dworkin et al., 2009 ), and that IFN-γ–neutralization in tacrolimus-treated mice abrogated SCC regression, significantly reducing CD8+ T-cell infiltration into SCC, and significantly impairing the secretion of CXCL9, CXCL10, and CCL5 within the tumor microenvironment ( Zeng et al., 2021 ). Other notable findings included reduced expression intensity of Mcl-1 in tacrolimus-treated RTRs compared with sirolimus-treated RTRs and ICPs ( Burke et al., 2015 ), augmented tumor growth in CsA-treated human cells lines through activation of TGFβ-activated kinase 1 (TAK1) ( Xu et al., 2011 ), and greater abundance of MMP-26 expression in cancer cells ( P = 0.04), and MMP-9 in neutrophils ( P = 0.005) in SCCs of patients taking CsA ( Table 4 ) ( Kuivanen et al., 2009 ).…”
Section: Resultsmentioning
confidence: 99%
“…Consistent with our findings, studies in other cSCC models found a dominant role of CD8 T cells and either no role or a supporting role for CD4 T cells. 40, 41, 42, 43 In other tumor models, CD4 T cells and MHC class II neoantigens are required for optimal responses to neoantigen-based immunotherapy or response to immune checkpoint inhibitors. 12, 14 A key difference in these models is that CD4 T cells contribute significantly to the anti-tumor immune responses, as depletion of CD4 T cells alone dramatically increases tumor growth.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is not surprising that CSCC tumors also respond to a range of immune therapies 7 . NK cells can directly interact with CSCC tumor cells 38 and CLEC2A‐positive fibroblasts to suppress tumor growth 39 . In addition, NK cells and Langerhans cells cooperate to suppress 1,12‐dimethylbenz(a)anthracene including tumor CSCC growth in mice 40 .…”
Section: Discussionmentioning
confidence: 99%